2018
DOI: 10.4067/s0717-95022018000200471
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Training Provokes Adaptations on Muscle Fibrosis of a Muscular Dystrophy Model

Abstract: SUMMARY:Duchenne muscular dystrophy (DMD) is a genetic neuromuscular disorder with progressive clinical signs until death, around the second decade of life. Mdx is the most used animal model to pre-clinical studies of DMD. Parameters of exercise on this muscular disease are still unknown. This research aimed to investigate if the low intensity treadmill training would exacerbate the markers of muscle injury, fibrosis, and the composition of the extracellular matrix by type I and III collagens of the mdx model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
5
Order By: Relevance
“…Several studies have shown that treadmill exercise can efficiently modulate this process. Indeed, a low intensity exercise, at a speed of 9 m/min for two months, on a horizontal platform reduces collagen deposition in limb muscles of mdx mice [ 73 , 74 , 75 ]. In addition, low intensity running induced a strong beneficial effect on the degeneration-regeneration process of mdx muscle and a shift in favor of regeneration, both in limb muscles and in diaphragm [ 76 , 77 ], and reduced the percentage of necrotic area in mdx soleus and gastrocnemius muscles, while it seemed to exert opposite effects on mdx plantaris muscle [ 78 ].…”
Section: Effects Of Exercise On Plastic Remodeling Of MDX Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that treadmill exercise can efficiently modulate this process. Indeed, a low intensity exercise, at a speed of 9 m/min for two months, on a horizontal platform reduces collagen deposition in limb muscles of mdx mice [ 73 , 74 , 75 ]. In addition, low intensity running induced a strong beneficial effect on the degeneration-regeneration process of mdx muscle and a shift in favor of regeneration, both in limb muscles and in diaphragm [ 76 , 77 ], and reduced the percentage of necrotic area in mdx soleus and gastrocnemius muscles, while it seemed to exert opposite effects on mdx plantaris muscle [ 78 ].…”
Section: Effects Of Exercise On Plastic Remodeling Of MDX Musclementioning
confidence: 99%
“…Based on the above reported experimental evidences, we can conclude that beneficial effects on mdx limb muscles induced by horizontal treadmill running exercise depend primarily on training intensity, being mainly associated to running speed ranging between 4 and 9 m/min. These positive effects, including fibrosis reduction, increased regeneration, improvement of muscle performances and structure, such as muscle hypertrophy and fiber type switch, seem to be not influenced by age, since they can be found in mdx mice 4–5 weeks old [ 108 , 109 ], 8 weeks old [ 74 , 76 , 77 , 110 ], and up to 20 weeks old [ 73 , 75 , 79 ], or by the duration of training, given the persistence of positive effects for exercise duration ranging between 1 and 6 months. On the contrary, horizontal treadmill exercise at higher intensity, with speed equal or greater than 12 m/min, or downhill/uphill running, generally exert detrimental effects on mdx muscles, and are often used to worsen the mdx phenotype before assessing the efficacy of drug treatment [ 8 , 81 , 82 , 84 , 87 , 92 , 99 ].…”
Section: Effects Of Exercise On Plastic Remodeling Of MDX Musclementioning
confidence: 99%
See 1 more Smart Citation
“…O saco vitelino (SV) é uma das membranas extraembrionárias presente em todas as espécies de vertebrados, importante para a sobrevivência inicial do embrião e representa uma promissora via de pesquisa em células tronco (MANÇANARES et al, 2015;PINTO et al, 2021). Sabe-se que células isoladas do SV humano durante o estágio embrionário foram capazes de expressar marcadores de CTM, além de conter hemangioblastos, células progenitoras do sistema vascular e hematopoiético (MANÇANARES et al, 2019).…”
Section: Terapia Celularunclassified
“…Estudos investigando o treinamento físico de baixa intensidade (low intensity training -LIT) em camundongos mdx encontraram resultados benéficos, como de melhora nos parâmetros fisiológicos, onde camundongos mdx treinados apresentaram uma redução dos níveis dos marcadores de estresse oxidativo (KACZOR et al, 2007;FERNANDES et al, 2019), redução de citocinas inflamatórias (HYZEWICZ et al, 2017) e foi capaz de modular proteínas envolvidas na defesa do estresse oxidativo (FONTANA et al, 2015). Camundongos mdx treinados também apresentam uma diminuição de áreas necróticas e infiltrados inflamatórios após treinamento (FRINCHI et al, 2014), além de apresentar uma menor área de fibrose intramuscular (GAIAD et al, 2017;PINTO et al, 2018;MORAIS et al, 2020).…”
Section: Introductionunclassified